2018
DOI: 10.1177/1753466618787380
|View full text |Cite
|
Sign up to set email alerts
|

The COPD Assessment Test (CAT) can screen for fatigue among patients with COPD

Abstract: Background:Fatigue is one of the most common symptoms among subjects with chronic obstructive pulmonary disease (COPD), but is rarely identified in clinical practice. The aim of this study was to evaluate the association between fatigue and health-related quality of life (HRQoL) assessed with clinically useful instruments, both among subjects with and without COPD. Further, to investigate the association between fatigue and the COPD Assessment Test (CAT)-energy question.Methods:Data were collected in 2014 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 32 publications
(70 reference statements)
1
37
0
2
Order By: Relevance
“…This study examined the relationship between symptom clusters and HRQoL. Psychological and physical symptoms, such as depression, anxiety, panic attacks, and fatigue-related symptoms, were significantly related to QoL in prior studies (Isselt et al, 2014; Pascal et al, 2017; Stridsman et al, 2018). In our study, symptom clusters 1 and 2 were significantly associated with HRQoL and almost all its subdomains, which is consistent with previous research.…”
Section: Discussionmentioning
confidence: 97%
“…This study examined the relationship between symptom clusters and HRQoL. Psychological and physical symptoms, such as depression, anxiety, panic attacks, and fatigue-related symptoms, were significantly related to QoL in prior studies (Isselt et al, 2014; Pascal et al, 2017; Stridsman et al, 2018). In our study, symptom clusters 1 and 2 were significantly associated with HRQoL and almost all its subdomains, which is consistent with previous research.…”
Section: Discussionmentioning
confidence: 97%
“…Factors such as depressive symptoms may potentially also contribute to the explanation of fatigue in patients with COPD. 12,13,18,50,51 Nevertheless, it may be difficult to distinguish if fatigue is a symptom of the depression itself, or emerges as an adverse effect of antidepressant drugs. Besides depressive symptoms, patients with COPD also often report poor sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that increased fatigue was related with frequency of acute exacerbations, hospitalizations, and in-creased length of stay. 21,22,24 Furthermore, elevated fatigue was related with high mental illness burden, which challenged patients coping resources and making fatigue as a symptom difficult to accept. 25 Thus, future studies need to focus on prospective randomized controlled trial to examine the effect of fatigue and healthcare costs in this patient group.…”
Section: Discussionmentioning
confidence: 99%